High loading single-atom Cu dispersed on graphene for efficient oxygen reduction reaction. (December 2019) - Han, Guokang; Zheng, Yu; Zhang, Xue; Wang, Zhiqiang; Gong, Yue; Du, Chunyu; Banis, Mohammad Norouzi; Yiu, Yun-Mui; Sham, Tsun-Kong; Gu, Lin; Sun, Yongrong; Wang, Yajing; et al.
Abstract: Single-atom metal dispersed on graphene materials are highly desired in various fields such as energy conversion/storage, catalysis and nanoelectronics. However, the fabrication of such materials with high loading level is still challenging, as the conventional pyrolysis protocol usually leads to metal agglomeration due to the poor thermal stability of metal precursors and the high surface energy of single-atom metals. Herein, we demonstrate the fabrication of single-atom Cu dispersed on graphene (Cu/G) with ultrahigh Cu loading of 5.4 wt%, using a unique confined self-initiated dispersing protocol. It is revealed that Cu is introduced into graphene matrix via highly active gaseous Cu-containing intermediate, which results in abundant and well-dispersed Cu-containing moieties. This Cu/G material with ultrahigh loading level as an electrocatalyst presents remarkable activity towards the oxygen reduction reaction (ORR) due to the abundant and highly dispersive Cu single atoms, even outperforming the commercial Pt/C. Our findings not only facilitate the development of single-atom metal dispersed on graphene materials but also highlight the importance of tuning active site structures in non-noble metal electrocatalysis. Graphical abstract: Image 1 Highlights: Single-atom Cu is dispersed on graphene by a unique confined self-initiated dispersing protocol. More than 5 wt% loading level of Cu single atoms on graphene is obtained (currently ~2 wt%). High loading level is achieved by a synergy between Cu and N in the gaseous intermediates. One of the best Cu-based catalysts for oxygen reduction reaction with a TOF of 0.116 e·site -1 ·s -1 at 0.85 V. Zn-air coin cell with Cu/G catalyst exhibits better performance than that with 20% Pt/C at the same loading.